Pemikiran Pendidikan Abdul Malik Karim Amrullah - Khoir, Mulyanto Abdullah; Jayyid, Difa’ul Fikri; Anshori, Nanang; Andannari, Rr. Meisara Putri (TSAQOFAH, 2025)
This paper explores the educational thought of Abdul Malik Karim Amrullah (HAMKA), a prominent scholar, intellectual, and literary figure who played a significant role in the reform of Islamic education in Indonesia. The purpose of this study is to present a brief biography of HAMKA, highlight the distinctive features of his educational philosophy, examine his contributions to the field of education, assess the relevance of his ideas in the current educational context, and identify his major written works. The research employs a library research method, collecting data from various sources such as books, journals, scholarly articles, and relevant documents. The findings reveal that HAMKA introduced substantial reforms in Islamic education, including its objectives, content, and methods. His educational philosophy is characterized by the integration of religious and secular sciences, an emphasis on character education, and the promotion of intellectual freedom to encourage critical thinking among students. His contributions include the establishment of early models of Al-Azhar schools, the Muhammadiyah University Prof. Dr. HAMKA (UHAMKA), and the Tablig School. HAMKA’s emphasis on character development and Islamic values remains highly relevant to the challenges of modern education. He authored over 80 works, with his most renowned contribution being the 30-volume Tafsir Al-Azhar. This study underscores the importance of actualizing HAMKA’s educational thought in the development of a contextual and sustainable Islamic education system.